2023
DOI: 10.1002/pmic.202300140
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive serum N‐glycan profiling identifies a biomarker panel for early diagnosis of non‐small‐cell lung cancer

Abstract: Aberrant serum N‐glycan profiles have been observed in multiple cancers including non‐small‐cell lung cancer (NSCLC), yet the potential of N‐glycans in the early diagnosis of NSCLC remains to be determined. In this study, serum N‐glycan profiles of 275 NSCLC patients and 309 healthy controls were characterized by MALDI‐TOF‐MS. The levels of serum N‐glycans and N‐glycosylation patterns were compared between NSCLC and control groups. In addition, a panel of N‐glycan biomarkers for NSCLC diagnosis was established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…Notably, the combination of the differentially expressed glyco-biomarkers demonstrated high sensitivity (85%) and specificity (86%) in predicting LC [132]. In our previous study, a panel of eight N-glycan structures showed satisfactory diagnostic performance for NSCLC, with an AUC of 0.86 in the validation set [133].…”
Section: N-glycan Markers In Cancermentioning
confidence: 83%
“…Notably, the combination of the differentially expressed glyco-biomarkers demonstrated high sensitivity (85%) and specificity (86%) in predicting LC [132]. In our previous study, a panel of eight N-glycan structures showed satisfactory diagnostic performance for NSCLC, with an AUC of 0.86 in the validation set [133].…”
Section: N-glycan Markers In Cancermentioning
confidence: 83%
“…N-glycome profile was characterized by a MALDI-MS based high-throughput analytical assay. 55 Profiling of Serum N-glycans were performed with the same manner as reported in our recent study, 56 , 57 including N-glycan release, chemical derivatization, MALDI-MS analysis and MS data processing.…”
Section: Methodsmentioning
confidence: 99%